Kvalitativna i kvantitativna analiza uratka na Bentonovom testu vidnog pamćenja kod bolesnika s mozgovnim oštećenjima - Nikčević-Milković, Anela (Array, 2000)
The aims of paper are:first:to examine whether Benton Visual Retention Test can be applied not only in diagnosing visual-perceptive, mnemonic and construction deficit, but also in differential diagnostics in patients with brain damage of different ethiology (traumas, tumors, vascular disorders) and different lateralisation of lesions (left and right brain hemisphere), and second:to find out wheter there are some differences in the test results regarding the sex of the tested persons. Having carried out individual tests on 95 patients with brain damage caused by trauma, cancer or vascular disorders in the KBC "Rebro", we have applied three criteria in the evaluation of the test results:the number of correct answers, total number of errors, and the type of errors. Based on a multiple ANOVA (2x2x3, lateralisation of damage x sex x type of brain damage), it has been determined that there are no significant F-rates for the two variables: number of correct answers and number of errors. No significant main effect of the diagnostic categories lateralisation of lesion and ex have been observed. The analysis of the type of errors shows only one significant F-ratio (F=5, 639, p=0, 020) in perseveration errors. More perseveration errors have been observed in patients with lesions in the left hemisphere (ML=1, 08) than in patients with lesions in the right hemisphere (MD=0, 62). No other main effects and no other interactions have been found to be significant. The obtained results lead to the conclusion that Benton Visual Retention Test can be recommended for diagnostics of deficiencies in the functions it examines, but it should not be applied for differential diagnostics, nor does it allow conclusions about the lateralisation of lesions.